Modulation of Aroma and Sensory Properties of Prokupac Wines by a Bacillus-based Preparation Applied to Grapes Prior to Harvest - Malićanin, M.; Danilović, B.; Cvetković, D.; Stamenković-Stojanović, S.; Nikolić, N.; Lazić, M.; Karabegović, I. (South African Journal of Enology and Viticulture, 2020)
Modern viticulture requires the replacement of hazardous agrochemicals with eco-friendly, bio-based products such as microbial preparations that enhance grape and wine quality while protecting the grapevine from pest and disease attacks. This study investigated the effects of a commercially available Bacillusbased preparation on the volatile and sensory properties of wines made from Vitis vinifera, cv. Prokupac grapes. Three different concentrations of preparation based on Bacillus subtilis Ch-13 were applied to grapevines two weeks prior to harvest. The total soluble solids in the grapes was affected by the application of B. subtilis Ch-1 and the alcohol content of the wine made from these grapes was greater. Wines made from the B. subtilis Ch-13-treated grapes showed an average increase in total phenolic compounds of about 27%, compared to the wine made from the untreated control grapes. The colour intensity of wines from the treated grapes, independently of the concentration, was higher by more than 30% than for the wine from the control grape sample. The B. subtilis Ch-13 treatment also affected the content of 3-methyl-1-butanol, ethyl decanoate and ethyl octanoate in the wine, at about 35%, 40% and 20%, respectively. The latter compounds are responsible for floral and fruity aromas. Generally, wines made from the treated grapes showed similar sensorial characteristics but scored better overall than the control. Principal component analysis showed a clear differentiation between wine made from the control and that from the B. subtilis Ch-13-treated grapes. The results suggest that the application of B. subtilis Ch-13 to grapevines two weeks prior to harvest has a positive effect on wine quality.